Investigation of Heavy Metal Pollution in Some Non-Edible Wild Plant Species Around the Old Chromium Mine Site in Köyceğiz District of Muğla Province - Yıldıztekin, Mahmut; Akbaş, Kenan; Tuna, Atilla Levent; Varol, Ömer (Journal of Anatolian Environmental and Animal Sciences, 2024)
In this study, the possible presence of heavy metals in the soil and wild plant species around the old Cr deposits of Köyceğiz-Dalyan Special Environmental Protection Area (Sandras Mountain) was investigated. Possible anthropogenic risk factors to which wild plant biodiversity is exposed are also the subject of this research. Fe, Cd, Co, Cr, Ni and Pb contents of soil, shoot and root samples of five wild plant species growing naturally in the region in question were investigated. These five species are: Alyssum masmenaeum (AM), Cytisopsis pseudocytisus (CP), Centaurea ensiformis (CE), Fumana aciphylla (FA), Phlomis angustissima (PA). The data obtained showed that heavy metals other than Ni, Cr and Co were found within normal limits in the soil samples. Particularly, soil Ni content is extremely high. Heavy metals except Ni, Cr and Fe were found within normal limits in shoot and root samples. One species (AM) for Ni and three species (FA, PA and CE) for Fe showed distinct hyperaccumulator properties. Ni hyperaccumulation detected in the Alyssum masmenaeum species is a particularly striking but well-known phenomenon. Since the research area has special environmental protection status, the soil structure and endemism of the region must be absolutely protected.